Magnetic Resonance Techniques Applied to the Diagnosis and Treatment of Parkinson’s Disease - de Celis Alonso, Benito; Hidalgo-Tobón, Silvia S.; Menéndez-González, Manuel; Salas-Pacheco, José; Arias-Carrión, Oscar (Frontiers in Neurology, 2015)
Parkinson’s disease affects at least 10 million people worldwide. It is a neurodegenerative disease which is currently diagnosed by neurological examination. No neuroimaging investigation or blood biomarker is available to aid diagnosis and prognosis. Most effort toward diagnosis using magnetic resonance has been focused on the use of structural/anatomical neuroimaging and diffusion tensor imaging. However, deep brain stimulation, a current strategy for treating Parkinson’s disease, is guided by magnetic resonance imaging. For clinical prognosis, diagnosis and follow-up investigations, blood oxygen level–dependent magnetic resonance imaging, diffusion tensor imaging, spectroscopy and transcranial magnetic stimulation have been used. These techniques represent the state of the art in the last five years. Here, we focus on magnetic resonance techniques for the diagnosis and treatment of Parkinson’s disease.